Leptin and leptin receptor expressions in prostate tumors may predict disease aggressiveness? - Osório,Clarice F. (2014)
PURPOSE: The aim of this study was to evaluate the expression of leptin and its receptor in histological sections of prostate tumors, and their association with prognostic factors. METHODS: A total of 532 surgical specimens from prostate cancer were studied. After histopathological diagnosis, the samples were included in tissue microarrays containing cores from tumor and non-tumor (benign prostatic hyperplasia) areas. These were immunostained with anti-leptin and anti-leptin-receptor antibodies. Objective and subjective analyses were performed. Student's-t-test and ANOVA were used to compare mean values, and linear regression was used to evaluate the correlation between histological results and prognostic indicators. RESULTS: Leptin receptor expression was reduced in tumors with a positive surgical margin, urethral margin involvement, and seminal vesicles invasion. Further, there was a negative correlation between the expression of leptin receptor in tumor areas and the sum of prognostic factors, suggesting that leptin receptor may predict the aggressiveness of disease. CONCLUSION: Our findings suggest that leptin receptor expression is a potential prognostic factor for PCa. Further investigation is needed to support the use of leptin receptor as a novel biomarker, although leptin itself does not seem to predict the aggressiveness of prostate cancer.